18th Latest Advances in Psychiatry Symposium. Issue 2 (13th May 2019) - David, Felix
Abstract : The 2019 Latest Advances in Psychiatry Symposium was held in March at the Royal College of Physicians, London, with the theme 'Mental health after Brexit: from psychosis to borderline personality disorders'. Here, Felix David covers highlights on the opioid overdose crisis, severe personality disorder, neurosurgery for severe mental illness, generalised anxiety disorder and burnout in medical staff.